Application development on Android phone I - Sng, Ping Yi. (2013)
Mobile phone has become an indispensable tool in our daily life. It is no longer just a communication medium but a computation device. Confidential personal data and important information are stored within the device. Protecting these personal and confidential data when the phone is stolen or lost has become a task of top priority.